Diffusion Characteristics of Toluene into Natural Rubber/Linear Low Density Polyethylene Blends - Henry C. Obasi; Okoro Ogbobe; Isaac O. Igwe (International Journal of Polymer Science)
The sorption and diffusion of toluene through blends of natural rubber (NR) and linear low density polyethylene (LLDPE) of varying compositions were studied at 35, 55, and 65°C by conventional weight-gain experiments. The effects of blend ratio on the diffusion, sorption, and permeation coefficients were determined. The sorption data were used to estimate the activation energies of diffusion and permeation, parameters which were found to show a decrease when the amount of NR or LLDPE was increased. The transport of toluene through most of the blends was anomalous, althouh at 35°C, the transport of toluene through the 60/40 blend was Fickian and at 35°C, pseudo-Fickian. The enthalpy of sorption of toluene obtained is positive and suggests a Henry's type sorption.